2011
DOI: 10.1039/c1cp21488h
|View full text |Cite
|
Sign up to set email alerts
|

Deeply bound cold caesium molecules formed after 0−g resonant coupling

Abstract: Translationally cold caesium molecules are created by photoassociation below the 6s + 6p(1/2) excited state and selectively detected by resonance enhanced two photon ionization (RE2PI). A series of excited vibrational levels belonging to the 0(-)(g) symmetry is identified. The regular progression of the vibrational spacings and of the rotational constants of the 0(-)(g) (6s + 6p(1/2)) levels is strongly altered in two energy domains. These deviations are interpreted in terms of resonant coupling with deeply bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 55 publications
(92 reference statements)
2
35
0
Order By: Relevance
“…2(a). Although the PA scheme essentially produces molecules in the a state, a fraction of those are stabilized in the X state through a two-photon decay process (equivalent to [7,16]). In order to quantify the number of molecules initially in the X state, we added the vibrational cooling to PA and obtained the spectrum shown in Fig.…”
Section: Simultaneouslymentioning
confidence: 99%
See 1 more Smart Citation
“…2(a). Although the PA scheme essentially produces molecules in the a state, a fraction of those are stabilized in the X state through a two-photon decay process (equivalent to [7,16]). In order to quantify the number of molecules initially in the X state, we added the vibrational cooling to PA and obtained the spectrum shown in Fig.…”
Section: Simultaneouslymentioning
confidence: 99%
“…We used transitions toward 0 − g (P 3/2 ), v = 6, J = 2 atν = 11665.2055 cm −1 [13] and 0 − g (P 1/2 ), v = 32 atν = 11158.5252 cm −1 [16] that respectively form molecules in 37 v a 50 and in the highest levels of the a state. The latter distribution is not transferred by our conversion scheme, which is consistent with the previously evoked poor FC factors between the a state and (2) 3 Π g .…”
Section: Simultaneouslymentioning
confidence: 99%
“…In Ref. [36] we have shown that the vibrational pumping toward v = 0 is very efficient only for low vibrational levels (v X < 10). This result is confirmed by computing, via a numerical simulation, the pumping efficiency from a given v X toward v X = 0 as shown in Figure 10.…”
Section: Rotational Coolingmentioning
confidence: 99%
“…The triplet ground electronic state, however, at the average distance 8.73 a 0 corresponds to the range of the repulsive wall so that only dissociating pairs could be formed. More recently, another mechanism of formation of cesium molecules in the ground singlet electronic state has been found [36]. In this mechanism, shown in Figure1b), the PA laser is set to excite long range vibrational levels belonging to the 0 − g (6s + 6p 1/2 ) state.…”
Section: Photoassociationmentioning
confidence: 99%
See 1 more Smart Citation